A leadless pacemaker in the real‐world setting: Patient profile and performance over time. Issue 1 (8th January 2023) - Roberts, Paul R.; Clémenty, Nicolas; Mondoly, Pierre; Winter, Stefan; Bordachar, Pierre; Sharman, David; Jung, Werner; Eschalier, Romain; Theis, Cathrin; Defaye, Pascal; Anderson, Christopher; Pol, Aimée; et al.
Abstract: Background: While prior Micra trials demonstrated a high implant success rate and favorable safety and efficacy results, changes in implant populations and safety over time is not well studied. The objective of this analysis was to report the performance of Micra in European and Middle Eastern patients and compare to the Micra Investigational Device Exemption (IDE) and Micra Post Approval Registry (PAR) studies. Methods: The prospective, single‐arm Micra Acute Performance European and Middle Eastern (MAP EMEA) registry was designed to further study the performance of Micra in patients from EMEA. The primary endpoint was to characterize acute (30‐day) major complications. Electrical performance was analyzed. The major complication rate through 12 months was compared with the IDE and PAR studies. Results: The MAP EMEA cohort ( n  = 928 patients) had an implant success rate of 99.9% and were followed for an average of 9.7 ± 6.5 months. Compared to prior studies, MAP EMEA patients were more likely to have undergone dialysis and have a condition which precluded the use of a transvenous pacemaker ( p  < .001). Within 30 days of implantation, the MAP EMEA cohort had a major complication rate of 2.59%. Mean pacing thresholds were low and stable through 12 months (0.61 ± 0.40 V at 0.24 ms at implant and 12 months). Through 12 months post‐implantation, the major complication rate for MAP EMEA was not significantly different from IDE ( p  = .56) or PAR ( p  = .79). Conclusion: Despite patient differences over time, the Micra leadless pacemaker was implanted with a high success rate and low complication rate, in‐line with prior reports. Abstract : The MAP EMEA study has shown that implantation of the Micra leadless pacemaker continues to remain a highly effective and safe procedure. This remains the case in both a traditional cohort of patients being considered for TV‐PPM and more specialized groups, such as those with renal impairment/hemodialysis, prior CIED infection or where conditions exist that preclude the use of TV‐PPM.